PEMBERDAYAAN MASYARAKAT DALAM MEMANAJEMENKAN EKONOMI LOKAL DENGAN MENGURANGI SAMPAH MELALUI PEMBUATAN TONG SAMPAH DI DESA OLAYAMA - Heriyanto Buulolo (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Waste issues in rural areas are often overlooked despite their significant impact on the community's quality of life. Olayama Village, Huruna District, is an example of an area facing significant challenges in waste management due to a lack of facilities and low environmental awareness. Furthermore, this village boasts untapped local economic potential. This study aims to analyze community empowerment efforts through locally-based waste management, utilizing the approach of making trash cans from natural materials such as bamboo and wood. The method used in this activity is a participatory approach involving KKN students and all levels of society in several stages: outreach, observation, production, distribution, and evaluation. The results of this activity indicate a significant increase in public awareness in maintaining environmental cleanliness, waste reduction, and the emergence of productive economic activities involving vulnerable groups such as the underprivileged and empowering the local economy. The resulting trash cans also become marketable commodities to the community, opening up opportunities for community economic development. This activity also encourages village government involvement in supporting similar programs in the future. The conclusion of this activity indicates that waste management not only solves environmental problems but can also be a gateway to sustainable local economic empowerment. Programs like this have the potential to be replicated in other villages, adapting them to their respective local potential and characteristics.